PERAN ORANG TUA DALAM PENGUATAN LITERASI DASAR MEMBACA DAN MENULIS SISWA - Wahyuni Arianti Djara Raba; Tanta Tanta; Kusdianto Kusdianto; Juliana Waromi; Yulius Mataputun; Petrus Irianto (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to describe and analyze the role of parents in strengtheing basic literacy in reading and writing among students of SD YPPGI Dome, Lanny Jaya Regency, Highland Papua Province. This research employs a descriptive qualitative method, with data collection techniques including interviews, observations, and documentation. The results show that parental involvement in strengthening basic literacy in reading and writing has not yet been optimal or evenly distributed. The study focuses on several aspects, including the role of parents as mentors, role models, facilitators, motivators, communicators, and providers of rewards and punishments, as well as the ssupporting and inhibiting factors and their impact on students’ basic literacy. Data analysis was conducted through data reduction, data presentation, and drawing conclusions.The role of parents as mentors and role models remains limited and inconsistent, while their role as facilitators is constrained by minimal learning resources and environment, particularly the conditions of the honai and limited electricity. The role of parents as motivators has the strongest influence on students’ learning enthusiasm and self-confidence. Communication between parents and teachers is still insufficient and not continuous, whereas parents’ role as providers of rewards and punishments has been carried out but is not yet fully educational. The main supporting factors are direct guidance, structured learning time, and emotional support, while the inhibiting factors include parents’ busyness, parents’ educational background, limited facilities, economic and geographic conditions, and weak school–parent communication. This study contributes conceptually to family literacy practices in 3T areas, based on the socio-cultural context of Highland Papua.